Device design rules and operation principles of high-power perovskite solar cells for indoor applications - Ann, Myung Hyun; Kim, Jincheol; Kim, Moonyong; Alosaimi, Ghaida; Kim, Dohyung; Ha, Na Young; Seidel, Jan; Park, Nochang; Yun, Jae Sung; Kim, Jong H. (Nano Energy, 2020)
In this work, we report on the design principles of high-power perovskite solar cells (PSCs) for low-intensity indoor light applications, with a particular focus on the electron transport layers (ETLs). It was found that the mechanism of power generation of PSCs under low-intensity LED and halogen lights is surprisingly different compared to the 1 Sun standard test condition (STC). Although a higher power conversion efficiency (PCE) was obtained from the PSC based on mesoporous-TiO2 (m-TiO2) under STC, compared to the compact-TiO2 (c-TiO2) PSC, c-TiO2 PSCs generated higher power than m-TiO2 PSCs under low-intensity (200–1600 Lux) conditions. This result indicates that high PCE at STC cannot guarantee a reliable high-power output of PSCs under low-intensity conditions. Based on the systemic characterization of the ideality factor, charge recombination, trap density, and charge-separation, it was revealed that interfacial charge traps or defects at the electron transport layer/perovskite have a critical impact on the resulting power density of PSC under weak light conditions. Based on Suns-VOC measurements with local ideality factor analyses, it was proved that the trap states cause non-ideal behavior of PSCs under low-intensity light conditions. This is due to the additional trap states that are present at the m-TiO2/perovskite interface, as confirmed by trap-density measurements. Based on Kelvin probe force microscopy (KPFM) measurements, it was confirmed that these traps prohibit efficient charge separation at the perovskite grain boundaries when the light intensity is weak. According to these observations, it is suggested that for the fabrication of high-power PSCs under low-intensity indoor light, the interface trap density should be lower than the excess carrier density to fill the traps at the perovskite's grain boundaries. Finally, using the suggested principle, we succeeded in demonstrating high-performance PSCs by employing an organic ETL, yielding maximum power densities up to 12.36 (56.43), 28.03 (100.97), 63.79 (187.67), and 147.74 (376.85) μW/cm2 under 200, 400, 800, and 1600 Lux LED (halogen) illumination which are among the highest values for indoor low-intensity-light solar cells.
Keywords: Charge transport layer; Electron transport layers; Ideality factors; Indoor light; Kelvin probe force microscopy; Power conversion efficiencies; Standard test condition (STC); Traps; Charge transport layer; Ideality factor; Indoor light; Perovskite solar cells; Traps